A research annual - Samuels, Warren J.; Biddle, Jeff (Research in the history of economic thought and methodology ;, 2001)
In addition to two sets of multiple reviews plus thirteen single reviews, this work includes three articles on the history of economic thought and one on methodology. The former are articles on the interpretation of Adam Smith, on Irving Fisher, and on certain economic aspects of the work of a literary figure, James Branch Cabell. The former is an article on econometricians' decision making as to choice of method. In addition, an important paper by Wesley Clair Mitchell on the money economy and economic efficiency is published with an interpretive introduction.